Loss-of-Function Mutation in Tryptophan Hydroxylase-2 Identified in Unipolar Major Depression - Zhang, Xiaodong; Gainetdinov, Raul R.; Beaulieu, Jean-Martin; Sotnikova, Tatyana D.; Burch, Lauranell H.; Williams, Redford B.; Schwartz, David A.; Krishnan, K.Ranga R.; Caron, Marc G. (Neuron (Cambridge, Mass.), 2005)
Dysregulation of central serotonin neurotransmission has been widely suspected as an important contributor to major depression. Here, we identify a (G1463A) single nucleotide polymorphism (SNP) in the rate-limiting enzyme of neuronal serotonin synthesis, human tryptophan hydroxylase-2 ( hTPH2). The functional SNP in hTPH2 replaces the highly conserved Arg441 with His, which results in ∼80% loss of function in serotonin production when hTPH2 is expressed in PC12 cells. Strikingly, SNP analysis in a cohort of 87 patients with unipolar major depression revealed that nine patients carried the mutant (1463A) allele, while among 219 controls, three subjects carried this mutation. In addition, this functional SNP was not found in a cohort of 60 bipolar disorder patients. Identification of a loss-of-function mutation in hTPH2 suggests that defect in brain serotonin synthesis may represent an important risk factor for unipolar major depression.